Tinospora sinensis (Lour.) Merr. (Menispermaceae) - a Hitherto Unreported Red Listed Medicinal Plant from Tamil Nadu State - Vijaya Sankar, R.; Ravikumar, K.; Ravichandran, P. (Indian Forester, 2004)
During botanical studies conducted in Thiruvannamalai District of Tamil Nadu State, India as a part of compilation ofthe district flora, Tinospora sinensis (Lour.) Merr. was collected from Javvadhu (’Javadi’) hills. It is a Red Listed mdicinal plant which also forms an addition to the Flora of Tamil Nadu. It is presented here in detail with nomenclature, description, distribution data, threat status and medicinal information.